Characterizations of Strong and Balanced Neutrosophic Complex Graphs - Narmada Devi, R.; Kalaivani, N.; Broumi, S.; A.Venkatesan, K. (International Journal of Engineering and Technology, 2018)
In this paper, the concepts ofÂ neutrosophic complex graph, complete neutrosophic complex graph, strong neutrosophic complex graph, balanced neutrosophic complex graph and strictly balanced neutrosophic complex graph are introduced. Some of the interesting properties and related examples are established.Â Â